PEMETAAN STAKEHOLDERS DALAM KEBIJAKAN PENANGANAN HIV/AIDS DI KABUPATEN KARANGANYAR - Octavian Chrisnugroho, Jericho; Rostyaningsih, Dewi; Zarkasyi Rahman, Amni (Journal of Public Policy and Management Review, 2024)
HIV/AIDS cases in Karanganyar Regency increase significantly every year. In 2024 the Health Departement of Karanganyar estimates an increase in cases of 941, but in April 2024 the increase in new cases of transmission is known to be 1315 new cases. The increase in HIV/AIDS transmission cases, needs to be a systematic and integrated attention and handling. The Karanganyar government has issued a policy regarding the handling of HIV/AIDS. The problems that arise are related to the extent of the role and influence of stakeholders in the implementation of HIV/AIDS handling policies in Karanganyar Regency. The purpose of this study is to map the role and influence of stakeholders in the implementation of HIV/AIDS handling policies to identify supporting and inhibiting factors of stakeholders in these policies. This study uses a descriptive qualitative research method. It identifies the roles and influences of key stakeholders involved in HIV/AIDS handling policies. The mapping analysis was carried out using three main attributes, namely power, urgency, and proximity. The results of the study find that coordination and collaboration between stakeholders are very important for the success of HIV/AIDS handling policies. Each stakeholder has its role and influence at different levels. In this study , the most striking stakeholder is the Health Departement as the primary of the policy. Conversely, the community and people living with HIV/AIDS (PLWHA) exhibit relatively lower levels of influence. This policy also involves NGOs engaged in the prevention and care HIV in Karanganyar Regency. Although existing stakeholders have been able to carry out their duties, there are still many obstacles found, including a lack of coordination between stakeholders, as well as stigma and discrimination against ODHA that is still high in the community. In this study, financial issues also arise, particularly delays in funding for the AIDS Control Commission. The delay in funding makes KPAD unable to run programs to support the implementation of this policy. The conclusion of this study is that the role of stakeholders is very crucial in the success of HIV/AIDS handling policies in Karanganyar Regency.